2006
DOI: 10.1038/sj.npp.1301235
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Desipramine Improves Cognitive Performance of Rats in an Attentional Set-Shifting Test

Abstract: Alterations in central monoaminergic neurotransmission are important in the actions of many antidepressants. This study tested the hypothesis that tonic elevation of noradrenergic (NA) neurotransmission in medial prefrontal cortex (mPFC) by chronic treatment with the selective norepinephrine (NE) reuptake blocker desipramine (DMI) may contribute to the beneficial cognitive effects of this antidepressant drug (AD). Male Sprague-Dawley rats were treated with DMI acutely (15 mg/kg, i.p.) or chronically for 21 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 56 publications
3
78
3
1
Order By: Relevance
“…It has been suggested that the functional consequence of downregulation of monoamine transporters is greater than pharmacological inhibition (Klimek et al, 1997) due to its noncompetitive nature vs the competitive nature of pharmacological inhibition. The results of the microdialysis experiment indicate that reduced NET expression does result in increased extracellular concentrations of NE, indicative of enhanced noradrenergic neurotransmission, similar to what is observed when the NET is inhibited acutely by desipramine (Lapiz et al, 2007a). Clinical actions of antidepressants develop gradually over weeks of treatment Katz et al, 1996Katz et al, , 2004, leading to the suggestion that neuroadaptive processes underlie the long-term behavioral effects.…”
Section: Discussionmentioning
confidence: 61%
“…It has been suggested that the functional consequence of downregulation of monoamine transporters is greater than pharmacological inhibition (Klimek et al, 1997) due to its noncompetitive nature vs the competitive nature of pharmacological inhibition. The results of the microdialysis experiment indicate that reduced NET expression does result in increased extracellular concentrations of NE, indicative of enhanced noradrenergic neurotransmission, similar to what is observed when the NET is inhibited acutely by desipramine (Lapiz et al, 2007a). Clinical actions of antidepressants develop gradually over weeks of treatment Katz et al, 1996Katz et al, , 2004, leading to the suggestion that neuroadaptive processes underlie the long-term behavioral effects.…”
Section: Discussionmentioning
confidence: 61%
“…Atomoxetine is more selective than the TCA and the lack of cholinergic and histaminergic effects seen with this drug may underlie the differences observed. Moreover, a larger impact on prefrontal NA is observed when DMI is administered chronically (Lapiz et al, 2006) and it is possible that the doses administered of acute DMI produced insufficiently effective increases in NA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several pharmacological studies have shown that drug-induced activation of the LC-NE system increases cognitive flexibility and behavioral disengagement. For example, drugs that increase tonic NE levels (i.e., mimic the effects of elevated NE release that characterize the tonic LC mode) have been found to improve attentional-set shifting and reversal learning in rats and monkeys (Seu, Lang, Rivera, & Jentsch, 2008;Lapiz, Bondi, & Morilak, 2007;Lapiz & Morilak, 2006;Steere & Arnsten, 1997;Devauges & Sara, 1990; but see Chamberlain et al, 2006). In humans, increased NE levels induced by the selective NE reuptake inhibitor atomoxetine have been found to improve the ability to stop an ongoing motor response when cued to do so (Chamberlain et al, 2006).…”
Section: Discussionmentioning
confidence: 99%